ASPEK-ASPEK PENDIDIKAN DALAM SALAT - Salamattang Salamattang (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2011)
There are a number of calls for prayer in the Qur’an and Prophetic Tradition. It is the second pillar of Islam and is of great importance to judge the level of belief of a Muslim. Each aspect of prayer contributes some values of education to develop good character in the society. Some researchers and personal experiences have pro-vided evidence of this. This study will discus some aspects of edu-cation derived from the movement of prayer in line with the Qur’an and Prophetic Tradition as well as the research findings and personal experience of others.